Characterization at nucleotide resolution of the homogeneously staining region sites of insertion in two cancer cell lines - Gibaud, Anne (Oxford University Press, 2013)
The mechanisms of formation of intrachromosomal amplifications in tumours are still poorly understood. By using quantitative polymerase chain reaction, DNA sequencing, chromosome walking, in situ hybridization on metaphase chromosomes and whole-genome analysis, we studied two cancer cell lines containing an MYC oncogene amplification with acquired copies ectopically inserted in rearranged chromosomes 17. These intrachromosomal amplifications result from the integration of extrachromosomal DNA molecules. Replication stress could explain the formation of the double-strand breaks involved in their insertion and in the rearrangements of the targeted chromosomes. The sequences of the junctions indicate that homologous recombination was not involved in their formation and support a non-homologous end-joining process. The replication stress-inducible common fragile sites present in the amplicons may have driven the intrachromosomal amplifications. Mechanisms associating break-fusion-bridge cycles and/or chromosome fragmentation may have led to the formation of the uncovered complex structures. To our knowledge, this is the first characterization of an intrachromosomal amplification site at nucleotide resolution.